FINANCIAL MANAGEMENT BEHAVIOR OF WORKING STUDENTS IN THE CREATIVE INDUSTRY IN SURABAYA - Felicia Angelica Manopo; Mariana Ing Malelak (Journal of Management Small and Medium Enterprises (SMEs), 2023)
This study examined the effect of financial knowledge and internal locus of control on financial management behavior with financial attitude as a mediating variable among working students in the creative industry in Surabaya. This study used a quantitative approach with a survey method obtained through an online questionnaire made with Google Forms. The analysis method used in this study is Structural Equation Modeling (SEM), with Partial Least Squares (PLS) using SmartPLS. Samples were chosen using the purposive sampling method so that the total sample size was 270 people. The results of this study proved that financial knowledge, financial attitude, and internal locus of control had a significant effect on financial management behavior. Also, financial attitude mediates the effect of financial knowledge on financial management behavior. However, the results of this study should be treated with caution due to the small sample size, which results in narrowing this study. Keywords: Financial Knowledge; Financial Attitude; Financial Management Behavior; Internal Locus of Control